Corredores de conservación - Burkart, Rodolfo; Varela, Diego; Schneider, Cristian; Aparicio, Gustavo (Revista Aves Argentinas, 2016)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).